A Novel Case of Symptomatic BK Viraemia in a Patient Undergoing Treatment for Hodgkin Lymphoma - Jacinta Perram; Jane Estell (Case Reports in Infectious Diseases)
Symptomatic BK viral infection in the immunocompromised host is well described, most commonly seen in renal transplant recipients, bone marrow transplant recipients, and HIV positive patients. The present case describes a novel clinical scenario of symptomatic urological BK virus infection in a patient receiving treatment for Hodgkin lymphoma. This case highlights the importance of casting a wide diagnostic net for adverse events encountered with novel therapeutic agents or regimens.